1998
DOI: 10.1063/1.476411
|View full text |Cite
|
Sign up to set email alerts
|

An infrared study of H8Si8O12 cluster adsorption on Si(100) surfaces

Abstract: Motivated by a controversy about the proper interpretation of x-ray photoelectron spectra of Si/SiO2 interfaces derived from the adsorption of H8Si8O12 spherosiloxane clusters on Si(100) surfaces, we have studied the adsorption geometry of the H8Si8O12 clusters on deuterium-passivated and clean Si(100) surfaces by using external reflection infrared spectroscopy. Access to frequencies below 1450 cm−1 was made possible through the use of specially prepared Si(100) samples which have a buried metallic CoSi2 layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
38
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 21 publications
7
38
0
Order By: Relevance
“…Valence band spectra were also obtained. The spectra show six key features between 7 and 17 eV that are identical with data previously obtained for H 8 Si 8 O 12 on Si(100) 7b 2 Soft X-ray Si 2p 3/2 core-level spectra of the interface derived from H 8 Si 8 O 12 chemisorbed to gold. …”
supporting
confidence: 82%
See 1 more Smart Citation
“…Valence band spectra were also obtained. The spectra show six key features between 7 and 17 eV that are identical with data previously obtained for H 8 Si 8 O 12 on Si(100) 7b 2 Soft X-ray Si 2p 3/2 core-level spectra of the interface derived from H 8 Si 8 O 12 chemisorbed to gold. …”
supporting
confidence: 82%
“…Monolayer assembly of discrete inorganic cage molecules has been reported during the past decade by a number of groups metal halide and polyhedral borane clusters on gold, , and hydridosilsesquioxane clusters on silicon, germanium, and zinc selenide , This line of research is also being utilized to elucidate the surface role of cage complexes in important technological areas such as catalysis, corrosion protection, low-temperature dielectric formation, and lithography …”
mentioning
confidence: 99%
“…The evidence for this is the coincidence of a measured reflection IR spectrum and a calculated one (by the method of density functional). 165 Calculations have shown that an H 2 O molecule changes its configuration insignificantly upon its transition on regular adsorption centres localised at the faces (100) of NaCl crystals. But if a molecule of H 2 O gets near an anion vacancy in the nearsurface monolayer of the crystal, its electronic density changes so much that the molecule dissociates.…”
Section: Deformation Of the Electronic Structure Over Adsorptionmentioning
confidence: 99%
“…The RAIRS spectrum of a thin chromium oxide film on chromium is shown (Fig. 3, spectrum 1) 30 and others on an Si(100) surface 31 . All of these features are consistent with the presence of HSiO 3 groups on the surface and the Si-O stretching frequency of 1175 cm À1 is indicative of intact spherosiloxane clusters and not amorphous SiO 2 .…”
mentioning
confidence: 99%
“…31 The sum total of the core-level XPS, valenceband and RAIRS data can be simply interpreted as the clusters bound via one or more silicon vertices to surface oxygen atoms. In principle, the Si-H bending mode can provide information on the symmetry of the bound cluster, and therefore the coordination mode to the surface.…”
mentioning
confidence: 99%